FAKTOR YANG BERHUBUNGAN DENGAN LAMA PERAWATAN PASIEN PASCA OPERASI KATARAK DI RAWAT INAP - Rezi Prima; Sisca Oktarini (Jurnal Keperawatan Abdurrab, 2023)
ABSTRACT Cataract is a cloudiness in the lens of the eye that results in impaired entry of light into the eye or retina which will result in a shadow on the retina or the retina is blurred. Cataracts can only be addressed through a surgical procedure. In postoperative patients after cataract surgery is recommended for treatment and stay in hospital 1-3 days. If it exceeds these days it will be detrimental to the hospital because the hospital tariff standard has been set by the government. This study aims to determine the factors associated with longer postoperative cataract patient care in hospital inpatient. Study design was a survey conducted by the analytical approach Retrosfektif Study. The population in this study were all patients after cataract surgery. The sample in this study was 61 people. The data was collected using medical record observation sheet. Data later on though is computerized by using univariate and bivariate analysis using the chi-square statistic. Test results showed less than half (24%) patients after cataract surgery are elderly parents, more than half (52%) the female fraction (7%) patients who have comorbidities and less than half (44%) patients after cataract surgery has long inpatient care in abnormal = > 3 days. The results of the statistical test known age p = 0.004, sex p = 0.025 and p = 0.313 comorbidities. In conclusion There is a significant relationship between age and sex with the duration of treatment post-cataract surgery and There is no significant relationship between comorbidities with a long post-operation cataract. Advice of health care is expected to continue efforts to improve care for patients post cataract surgery. Keyword: Sex, Treatment, Comorbidities And Age